2016
DOI: 10.1007/s12161-016-0441-6
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Azodicarbonamide in Flour Using Near-Infrared Spectroscopy Technique

Abstract: Abstracts Azodicarbonamide is wildly used as a flour gluten fortifier in many countries, but according to the research results of toxicology of azodicarbonamide, its acute toxicity is slightly toxic. A dosage of 10 g/kg is lethal to mice, and it was proved by some researches to be dangerous or unhealthy for people and not suitable to be added in flour; hence, there is a need to identify the concentration of azodicarbonamide in flour quickly. Compared to traditional methods like highperformance liquid chromatog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The results indicated that the R 2 values of lime and calcium carbonate using the PLS algorithm were 99.80% and 96.98%, the RMSEC were 0.19 and 0.34, the RMSECV were 0.26 and 0.75, the RMSEP were 0.63 and 0.44, and the RPD were 8.57 and 5.24, respectively. In terms of azodicarbonamide (ADA) detection, Gao et al (2016) utilized NIR spectroscopy in combination with RBF to quantitatively detect the content of ADA in wheat flour. The established model presented good prediction indicators, with R, RMSEP, and RPD values of 0.97828, 18.2887 mg/kg, and 4.7621, respectively.…”
Section: Safety Analysis Of Wheat Flourmentioning
confidence: 99%
“…The results indicated that the R 2 values of lime and calcium carbonate using the PLS algorithm were 99.80% and 96.98%, the RMSEC were 0.19 and 0.34, the RMSECV were 0.26 and 0.75, the RMSEP were 0.63 and 0.44, and the RPD were 8.57 and 5.24, respectively. In terms of azodicarbonamide (ADA) detection, Gao et al (2016) utilized NIR spectroscopy in combination with RBF to quantitatively detect the content of ADA in wheat flour. The established model presented good prediction indicators, with R, RMSEP, and RPD values of 0.97828, 18.2887 mg/kg, and 4.7621, respectively.…”
Section: Safety Analysis Of Wheat Flourmentioning
confidence: 99%
“…To date, many methods have been developed for the determination of ADA in flour, but most of them require sophisticated/expensive instrument and time-consuming pretreatment, which lead to a longer analysis time and higher cost. Compared with these methods, our method has obvious analytical advantages such as low cost, short analysis time, and instrument-free, which is suitable for the rapid and on-site detection of ADA in flour sample.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Currently, the main methods used for the detection of ADA in flour included direct methods and indirect methods. Direct methods included infrared spectrometry (IR), Raman spectrometry, capillary electrophoresis, and high performance liquid chromatography (HPLC). Indirect methods are those by which ADA was first converted into semicarbazide hydrochloride, and then the semicarbazide hydrochloride was determined with liquid chromatography coupled with mass spectrometry (LC-MS) or enzyme linked immunosorbent assay (ELISA). , Both direct and indirect methods have obvious shortcomings such as laborious and time-consuming pretreatment of sample, sophisticated and expensive instrumentation, and higher cost, and do not meet the requirement of rapid and on-site detection. Recently, some rapid methods have been developed for the detection of ADA in food based on surface-enhanced Raman spectroscopy (SERS). , However, these rapid methods also require sophisticated instruments and have higher cost.…”
mentioning
confidence: 99%
“…As the optoelectronic technology develops, some spectroscopy methods have been shown reliable in the detection of wheat flour additives, such as fluorescence spectroscopy [Chen et al, 2011], Raman spectroscopy [Cebi et al, 2017], near-infrared spectroscopy [Che et al, 2017;Gao et al, 2016], and terahertz spectroscopy [Hu et al, 2020;Sun et al, 2019]. However, these spectral methods only obtain the information of a single sampling point, which poses the problem of sampling representativeness.…”
Section: Introductionmentioning
confidence: 99%